PENATAAN LEMBAGA NEGARA REFLEKSI PENGUATAN SISTEM PRESIDENSIAL - Abustan Abustan (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
The amendment of Article 1 Paragraph (2) of the 1945 Constitution of the Republic of Indonesia indicates the affirmation of Article 4 Paragraph (1) of the 1945 Constitution of the Republic of Indonesia, namely the affirmation of a presidential government system by affirming the position of the President as head of state as head of government of government) can not be separated and elected directly by the people, so that the President has the authority as